Against ethnomusicology: Language performance and the social impact of ritual performance in Islam. (1st December 2013) - Frishkopf, Michael
This article argues that 'music' is unsatisfactory to reference sounds of ritual performance in Islam, not only because the term has been controversial for Muslims, but especially due to its unremovable pre-existing semantic load centred on non-referential aesthetic sound, resulting in drawing of arbitrary boundaries, incompatibility with local ontologies and under-emphasis on the referential language lying at the core of nearly all Islamic ritual. From the standpoint of the human sciences, this study is interested in the understanding of such rituals as combining metaphysical and social impact. Use of 'music' tends to distort and even preclude holistic ritual analysis capable of producing such understanding. As a result, ethnomusicology is misdirected. Theoretically and methodologically, this article develops an alternative concept, 'language performance' (LP), including four aspects – syntactic, semantic, sonic and pragmatic – especially designed for Islamic ritual performance. Applying a linguistic theory of communication developed by Jakobson, it shows how LP can be developed as a comprehensive, descriptive framework for comparative ritual analysis, akin to Lomax's global Cantometrics, but avoiding its flaws through a more flexible design and modest scope, enabling systematic, comparative investigations of performance in Islamic ritual. The article closes with an example of such analysis centred on Sufi rituals in contemporary Egypt.